Can bulk-fill resin restorations be an alternative to resin-modified glass ionomer cement restorations in primary molars of toddlers? A randomized clinical trial protocol - Isabela Coelho Novaes; Luna Chagas Clementino; Fernanda Morais Ferreira; Tathiane Lenzi; Marco Aurélio Paschoa; Saul Martins Paiva; Fernanda Bartolomeo Freire-Maia; Paulo Antônio Martins-Júnior (Universidad de Concepción., 2021)
Background: The aim of this study was to elaborate a randomized clinical trial protocol to evaluate the effectiveness of class I restorations in resin-modified glass ionomer cement (RMGIC) and bulk-fill resin in primary molars with untreated early childhood caries in toddlers. Material and Methods: A total of 59 toddlers up to 36 months old with at least two primary molar teeth with untreated dental caries of single surface on different sides of the mouth will be selected at the Pediatric Dentistry Clinics of the Faculty of Dentistry at Federal University of Minas Gerais (UFMG), Brazil. Teeth with untreated dental caries in the left and right sides of each patient's mouth will be randomly distributed into 2 groups: Group 1 (Control): encapsulated RMGIC restoration with Riva light cure (SDI, Florida, USA) and Group 2 (Test): Filtek bulk-fill composite resin restoration (3M/ESPE, St. Paul, USA) with universal single bond adhesive system (3M/ESPE, St. Paul, USA). A single trained dentist will perform all restorative procedures. The restorations will be evaluated after 1, 6, 12, 18 and 24 months by two trained and calibrated examiners. Cost-efficacy analysis will be carried out. Kaplan-Meier survival analysis, Log-rank test, Cox regression, Poisson regression analysis, Mann-Whitney test or Kruskal-Wallis will be performed to analyze data. Conclusion: The protocol will make it possible to determine the most efficacy material for the restoration of cavities in cavities in primary molars of toddlers.